TEAM GAMES TOURNAMENT (TGT) TYPE COOPERATIVE LEARNING MODEL USING SNAKES AND LADDERS MEDIA TO IMPROVE MATHEMATICS LEARNING OUTCOMES OF GRADE IV STUDENTS OF MI DARUSSALAM - Shandra Ria (CV Grasta Glory, 2026)
Low mathematics learning outcomes among elementary school students are often caused by limited student engagement and the use of less interactive learning models. To overcome this issue, cooperative and game-based learning approaches are needed. This study aims to examine the effectiveness of the Team Games Tournament (TGT) cooperative learning model assisted by snakes and ladders media in improving the mathematics learning outcomes of fourth-grade students. This research employed Classroom Action Research (CAR) conducted at MI Darussalam Lubuklinggau with 28 fourth-grade students. The study was carried out in two cycles, each consisting of planning, action, observation, and reflection stages. Data were collected through tests, observations, and documentation, and analyzed using descriptive quantitative techniques. The results showed a significant improvement in students’ mathematics learning outcomes. The average score increased from 60 in Cycle I to 77.28 in Cycle II, along with an increase in learning mastery. These findings indicate that the TGT model supported by snakes and ladders media effectively enhances students’ mathematics learning outcomes. This study recommends the use of game-based cooperative learning models in elementary mathematics instruction and suggests further research on different materials or grade levels.